Análise de conteúdo do mercado de ensino sacerdotal de umbanda, na perspectiva yorùbá por meio do “tridente de Èṣù” (2002 – 2022) - Moraes, Maxwell Azevedo Viana (2023)
Umbanda, as a religion with an African presence, went through numerous processes of distancing itself from its black origin, mainly emphasized from the beginning of the 20th century. Such a context offers us the possibility of understanding the changes that religion has undergone and continues to undergo. Therefore, guided by the conception of the Yorùbá tradition, we will seek to carry out a content analysis of priestly education courses, with promises of access to countless knowledge, thus corresponding to the desires of our current liquid society. Thus, the current research aims to verify, through Content Analysis by Laurence Bardin (1977), the publications of such courses, based on the debate on life and liquid modernity and the volatility of contemporary capitalist society by Zygmunt Bauman (2001; 2007), the presence of individualism and its reflections in our society, through Gilberto Velho (1981) and the debates of Mary Douglas (2004) that will help us understand the world of consumer goods and capitalist relations. African tradition and morality will be our references through the writings of John Mbiti (1975), and specifically on the conception of the family of saints, we will be based on Vivaldo da Costa Lima (2003), where the nuances of ethics in Èṣù and the traditional Yorùbá vision, will be verified through the lines of Síkírù Sàlámì (2015) and Ronilda Iyakemi Ribeiro (2022).